Regional Languages under the Shadow of the National Language: Shifting Linguistic Identity among Indonesian Youth - Nurhalizah (Punggawa Global Research: Jurnal Multidisiplin, 2026)
Regional language shift in Indonesia is often treated as a matter of declining speaker numbers, endangered linguistic diversity, or insufficient preservation. Such a view remains important, but it does not fully explain why many young Indonesians still feel attached to regional languages while using Bahasa Indonesia more comfortably in school, peer interaction, mobility, and digital communication. Drawing on secondary data from language policy documents, official vitality reports, prior academic studies, and publicly accessible digital discourse, this article examines regional language shift as a reconfiguration of youth linguistic identity. The analysis shows that Bahasa Indonesia gains social strength because it travels easily through institutions and mixed public settings, while regional languages are increasingly valued through family memory, cultural recognition, and selective performance. Among young speakers, attachment to regional language often survives, but ordinary usability becomes weaker when the language is no longer supported by daily family routines, peer legitimacy, and public confidence. Digital spaces renew regional linguistic identity by making local expressions visible and shareable, yet this renewal remains ambivalent when visibility depends on fragments rather than sustained use. The article argues that revitalization needs to move beyond symbolic pride and rebuild the social conditions that allow regional languages to function as ordinary media of youth interaction.